Implementasi Pembelajaran IPS Berbasis Multikultural di SMP TQ Annida Kota Salatiga - Alfatah, Akhid Ilyas; Seviyanti, Seviyanti (IJTIMAIYA: Journal of Social Science and Teaching, 2022)
Cultural diversity is a natural thing. Multicultural learning makes students aware of their cultural diversity, and respects other cultures. This study aims to describe the stages of multicultural learning in social studies subjects in class VII SMP TQ Annida Salatiga. The research method is a qualitative research method. primary data source from observations of social studies learning activities. While the secondary data sources are the results of interviews with school principals and seventh grade teachers as well as archives of learning activities. The results of this study are the stages in multicultural learning include analysis of potential factors before learning; establish learning strategies in the form of dialogue, observation, and case handling; and develop multicultural-based learning plans. The final conclusion shows that social studies learning uses student centered; its implementation through discussion, role playing and demonstration; and the multicultural learning is more oriented towards the surrounding environment.